DAMPAK INDUSTRI PENGOLAHAN KAKAO (Theobroma cacao L.) TERHADAP PENDAPATAN PETANI DI GAPOKTAN â€œKUMPUL MAKARYOâ€ NGLANGGERAN, PATUK, KAB. GUNUNGKIDUL, YOGYAKARTA - Nur Afni Sofia; Slamet Hartono; Ignatius Suprih Sudrajat (Fakultas Pertanian UST, 2019)
Â Â This study aims to determine and analyze the income of cocoa farmers (Theobroma Cacao L) after there is a cocoa processing industry in Langgeran Village, Patuk District, Gunung Kidul Regency and the difference of farmer's income before and after the industry is there. The hypothesis is that the cocoa processing industry has a positive impact for farmersâ€™ in its Gapoktan. The basic method used is descriptive method. The sampling method used Simple Random Sampling with the numbers of respondents are 68 people. The analytical method used income analysis and hypothesis testing with different T-test average tests (Independent sample T-test). The results of the study stated that the income after the cocoa processing industry existed is about Rp 4,727,549 and it has a positive impact for farmersâ€™ income in the